Efficient point-by-point manipulated visible meta-vortex-lenses with arbitrary orbital angular momentum. (18th October 2019) - Liang, Yaoyao; Li, Boyao; Meng, Zhao; Zhao, Lin; Mao, Min; Liu, Hongzhan; Wei, Zhongchao
Abstract: The ability of light to carry and deliver orbital angular momentum (OAM) in the form of optical vortices has attracted much interest. Conventional optical vortices are usually generated by bulky or expensive devices, which would sharply decrease the integration of optical communication systems. Here we demonstrate efficient large-area wavelength-thick metasurfaces that have the ability to produce high-quality optical vortexes with arbitrary OAM and to focus the beams into wavelength-scale rings with efficiency as high as 80%. Moreover, we reveal the relationship between size and energy distribution of focal rings (FR) with different OAMs: as the number of OAM increases, the size of the FR is linearly increasing, the peak focusing intensity (FFI) is decreasing in inverse proportional type, while the total energy on the FR remain almost unchanged. Rigorous quantitative analysis about the coupling effect among nanoantennas and the chromatic aberrations of the proposed metasurfaces are further discussed. We envision such highly efficient metasurfaces for spiral focusing will have potential applications in optical tweezers and communications.